Ramifications the crisis Fiscal 2020 is on Economy The Iraqi - Basima kzar Hassan (Eximia, 2024)
It shook the crisis Finance Globalism Entities countries a lot, but Iraq did not It is not One of them, And that The Iraqi economy is not linked to the global economy, in addition to the absence of foreign investments for many years in a country that is considered second in the world in terms of its oil reserves. So it must Iraq must exploit the financial crisis, which has affected most of the economies of various countries, in order to establish infrastructure by taking advantage of the decline in global prices for all materials used in construction and reconstruction operations. The country will be greatly affected by this crisis in the coming period unless possible preventive measures are taken to limit losses . It is important to reconsider monetary policy and take care of reforms in various sectors, as well as adopting thoughtful development approaches that enable the country to avoid external economic and financial shocks